How to kidnap the rich : a novel - Raina, Rahul (Harper Perenial, 2021)
Meet Ramesh Kumar, "examinations consultat," who makes a lucrative living taking tests for the sons of India's elite. He is just a cog in the wheel that keeps the middle classes thriving, until he takes India's national university entrance exam for a lackluster student and inadvertently comes in first. Ramesh sees an opportunity--perhaps even an obligation--to cash in on the newfound celebrity of his client Rudi, who's soon juggling stardom and his new job as the host of a quiz show. They young men's meteoric rise brings material wealth and romantic intrigue, until they're both kidnapped and held for ransom. But the way out of their predicament will lead Ramesh and Rudi through a maze of crimes both large and small, their dizzying journey revealing a modern India in all its complexity, squalor, and beauty.